Training Significantly Improves Fetoscopy Performance: A Pilot Randomized Controlled Trial - Mietzsch, Stefan; Boettcher, Johannes; Yang, Sisi; Chantereau, Pierre; Romero, Philip; Bergholz, Robert; Reinshagen, Konrad; Boettcher, Michael (European Journal of Pediatric Surgery, 2016)
Background Implementation of complex fetoscopic procedures that included intracorporeal suturing has been limited due to technical difficulties that might be surmounted with adequate training. Evaluating the impact of laparoscopic or fetoscopic training on fetoscopic performance was the aim of this study.Methods To evaluate fetoscopic performance after either laparoscopic or fetoscopic training, subjects were asked to perform four surgeon's square knots fetoscopically prior and post 2 hours of hands-on training. All subjects were medical students and novice in laparoscopic and fetoscopic interventions. Total time, knot stability (evaluated via tensiometer), suture accuracy, knot quality, and fetoscopic performance were assessed.Results Forty-six subjects were included in the study; after simple randomization, 24 were trained fetoscopically and 22 laparoscopically. Both groups had comparable baseline characteristics and improved after training significantly regarding all aspects assessed in this study. Subjects who trained fetoscopically were superior in terms of suturing and knot-tying performance.Conclusion Training significantly improves fetoscopic performance and may indeed be the keystone for future complex fetoscopic interventions. It seems advisable to train rather fetoscopically than laparoscopically resulting in higher suture and knot-tying quality.
Keywords: laparoscopy; fetoscopy; training